2020
DOI: 10.1186/s12875-020-01195-w
|View full text |Cite
|
Sign up to set email alerts
|

‘Very brief advice’ (VBA) on smoking in family practice: a qualitative evaluation of the tobacco user’s perspective

Abstract: Background: Very Brief Advice on smoking (VBA) is an evidence-based intervention designed to increase quit attempts among patients who smoke. VBA has been widely disseminated in general practice settings in the United Kingdom, however its transferability to Southern European settings is not well established. This study sought to document the perspectives of Greek general practice patients in terms of the acceptability and satisfaction with receiving VBA from their general practitioner (GP) and its influence on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…Secondly, people may periodically update their beliefs and intentions and it is important to provide support throughout the choice process. This may concern information about vaccination through reliable channels i.e., medical experts on mass or social media, or targeted very brief advice (VBA) from general practitioners or professional patient associations [ 12 ]. Such a conversation with a reliable advisor or doctor may be even more effective if local trust in government (and its institutions) is low [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, people may periodically update their beliefs and intentions and it is important to provide support throughout the choice process. This may concern information about vaccination through reliable channels i.e., medical experts on mass or social media, or targeted very brief advice (VBA) from general practitioners or professional patient associations [ 12 ]. Such a conversation with a reliable advisor or doctor may be even more effective if local trust in government (and its institutions) is low [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…These health care teams could be trained and serve as a collaborative approach in the identification and management of patients with cognitive impairment. Recent experience on other research topics indicated that intervention projects within the context of Greek primary care could be successfully implemented (67).…”
Section: Implication For Research Education and Clinical Practicementioning
confidence: 99%
“…A smoking cessation course was not a specific part of the design in the programme.The participants were informed about local smoking cessation courses and given cards with contact information. A systematic review and meta-analysis by Papadakis et al concludes that the method "Very brief advice" where the initiative and direct registration to a smoking cession course is taken by the healthcare provider without giving any advice is effective, 31 and this method may have improved the outcome.…”
Section: Discussionmentioning
confidence: 99%